Generous and Ungenerous Contracts: Case Study of the Artist William Powhida's Grevsky and Store-to-Own Contracts. Issue 3 (4th May 2022) - Whitaker, Amy
ABSTRACT: This paper investigates the case study of William Powhida and two different contracts that the artist developed: first, the intentionally draconian contracts that the artist developed within an artwork, Grevsky, to force artists into subordinating their intellectual property position to commodification, and second, the contract that the artist William Powhida, the person, developed to ask his friends to help him store art. Applying Grant's (2013 ) framework of givers, takers, and transactors, this paper presents a conceptual framework of ungenerous and generous contracts. The paper makes the argument that economic awareness, legal strategy, and a spirit of friendship can co-exist and that draconian contracts are rarely needed in an arts context in which stakeholders are likely to have shared interests in both sides of a contract. This analysis presents a more generalizable framework of non-zero-sum contractual negotiation in relation to the artistic and financial nature of works of art, as well as an argument for the importance of rhetoric and contractual structures of collaboration and friendship. These contractual questions become increasingly important as artists employ self-executing "smart" contracts for blockchain-based or non-fungible token (NFT) works, and as artists continue to rely on contracted freelance work. The increased reliance on digital working conditions creates higher stakes rights management given likelihood of recording.